Aspek Biologi dan Potensi Lestari Sumberdaya Lobster (Panulirus spp.) di Perairan Pantai Kecamatan Ayah Kabupaten Kebumen - Muammar Kadafi; Retno Widaningroem; Soeparno Soeparno (Jurnal Perikanan Universitas Gadjah Mada, 2006)
The research on biological aspects and maximum sustainable yield of spiny lobster (Panulirus spp.) in Ayah coastal waters Kebumen Regency aimed to know biological aspects (including species of lobster, length-weight relationships, and sex-ratio), maximum sustainable yield, and exploitation rate of spiny lobster. Biological data were collected in January-February 2004 with census and survey methods. Production and effort data between 1998 to 2003 were used to estimate maximum sustainable yield of spiny lobster. This research found six species of lobsters (Panulirus homarus, P. ornatus, P. penicillatus, P. longipes, P. versicolor, and P. polyphagus). Length-weight relationships based on the sex and carapace length showed isometric and allometric growth models. Male and female ratio was 1,06:1. The maximum sustainable yield was 19,498 kg/year and the exploitation in this area was already overfished.